2001
DOI: 10.1152/ajpcell.2001.280.2.c317
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines in pancreatic islets of obese-hyperglycemic (ob/ob) mice of different ages

Abstract: To further evaluate the role of polyamines in insulin production and cell replication in diabetic pancreatic islets, we have studied hyperplastic islets of obese-hyperglycemic mice of different ages and normal islets of the same strain. The aims of the study were to investigate the impact of the diabetic state and aging on polyamine contents and requirements in these islets. Cultured islets from lean and obese animals contained significantly less polyamines than freshly isolated islets. Spermine-to-spermidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In fact, emerging evidence suggests that increased levels of polyamines in white adipose tissue, liver or skeletal muscle could stimulates energy expenditure and confer resistance to diet-induced obesity and non-alcoholic fatty liver disease (147, 148). In addition, a number of studies using different obesity animal models have reported altered levels of polyamines in adipose tissue (150), liver (151, 152), pancreatic islets (153), and urine (154). In addition, blood polyamines have been shown to be significantly higher in obese children compared to non-obese controls (155).…”
Section: Polyamines In Obesity and Related Metabolic Disordersmentioning
confidence: 99%
“…In fact, emerging evidence suggests that increased levels of polyamines in white adipose tissue, liver or skeletal muscle could stimulates energy expenditure and confer resistance to diet-induced obesity and non-alcoholic fatty liver disease (147, 148). In addition, a number of studies using different obesity animal models have reported altered levels of polyamines in adipose tissue (150), liver (151, 152), pancreatic islets (153), and urine (154). In addition, blood polyamines have been shown to be significantly higher in obese children compared to non-obese controls (155).…”
Section: Polyamines In Obesity and Related Metabolic Disordersmentioning
confidence: 99%
“…This effect was blocked by a Ca 2þ chelator, BAPTA-AM, and by an inhibitor of a Ca 2þ -dependent protease, calpain. These demonstrated that excessive NO production induces apoptosis, wherein an increase in [Ca 2þ ]i and resultant activation of calpain play a key role (Sjoholm et al, 2001). Whereas, alterations in cytosolic Ca 2þ homoeostasis do have a significant role in certain forms of beta-cell death, Bai et al demonstrated they do not contribute to the pathway of apoptosis evoked by hA in islet beta-cells (Nakata et al, 1999).…”
Section: First Stage: Genetic Reprogrammingmentioning
confidence: 99%
“…In transgenic mouse models, the dysregulation of polyamine metabolism has been shown to impact glucose, lipid and energy homeostasis [9,10,11,12,13,14]. In addition, a number of studies using animal models of obesity have reported impaired levels of polyamines in adipose tissue [15], liver [16,17], pancreatic islets [18], and urine [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the pancreas, polyamines are mainly located within the secretory granules of the islet β cells [30], where they have been implicated in proinsulin biosynthesis and insulin secretion [31]. Islet polyamine levels diminish with both age and obesity [18], suggesting that alterations in the intracellular levels of polyamines might affect β cell function. Remarkably, transgenic mice which overexpress the polyamine catabolic enzyme spermidine/spermine acetyltransferase (SSAT), which contains higher levels of putrescine and reduced levels of spermidine and spermine in the pancreatic islets, display impaired glucose-stimulated insulin secretion [11].…”
Section: Introductionmentioning
confidence: 99%